A study of double layer conical porous hybrid journal bearing operated with non-Newtonian lubricant. (January 2023) - Sharma, Satish C.; Singh, Anil
Abstract: This study deal with the numerical simulation of a hybrid double layer conical porous bearing (DCPB) considering the synergistic effects of a double layer porous matrix and non-Newtonian lubricant (cubic law model) behaviour. The present study investigates the interactive effects of the non-linear factor of lubricant, permeability parameter and semi cone angle on the performance of a hybrid DCPB. The modified Reynolds equation is solved using the finite element technique for a hybrid DCPB. Findings of this study indicate that the DCPB improve the performance parameters as compared to hybrid single layer conical porous bearing (SCPB). Further, the use of non-Newtonian lubricant improves the stability threshold speed margin ω ̅ th and reduces the frictional power loss ( p ̅ fric ) . Highlights: DCPB with synergistic effect of double layer porous matrix and non-Newtonian lubricant (cubic law model) is computed. Finite element analysis of double layer conical porous hybrid journal bearing is performed. The interactive effects of semi cone angle, non-linear factor of lubricant and permeability parameter has been studied. Performance of bearing in terms of static and dynamic characteristics for different values of radial load W ̅ r .